Unraveling the Nexus: Exploring the Pathways to Combined Resource Use. (13th February 2018) - Font Vivanco, David; Wang, Ranran; Deetman, Sebastiaan; Hertwich, Edgar
Summary: In response to the unprecedented decline in global natural resource endowments, the so‐called nexus framework is gaining increasing influence on resource management practices. In this research, we approach the resource nexus through the concept of nexus pathways. Nexus pathways are configurations that resource flows follow along supply chains leading to the combined use of two or more resources. Three general types of pathways are identified: direct (on‐site use), dependent (one‐way supply chains), and interdependent (supply‐chain feedbacks). We quantify and compare each pathway by means of multiregional input‐output analysis and structural path analysis, and apply this approach to a comparative case study on the water‐energy nexus (WEN) in the United States and China. Interdependencies or feedbacks are generally thought to be relevant for the WEN, especially between water and energy sectors. Our economy‐wide analysis for both countries indicates, however, that feedbacks neither play an important role in the WEN nor substantially take place between water and energy sectors. The most important feedbacks contribute to less than 1% of total resource use, and these take place mostly between manufacturing sectors. Overall, the studied WEN is mostly driven by dependent pathways and, to a lesser degree, direct resource use. Comparative differences between the two countries are largely explained by differences in economic structure, technology, and resource endowments. Our findings call into question current research and policy focus and suggest greater attention to less complex, but more determining, pathways leading to absolute resource use.